A quasi-experimental method for testing rural design support within a DRM framework. Issue 2 (7th May 2019) - Smits, Michaël Willem Maria
Abstract : Purpose: The purpose of this paper is to describe the quasi-experiment setting to test the formulated design support (developed in the author's PhD research) within a design research methodology (DRM) framework. This support intends to help designers to consciously engage rural families within a development aid scenario and increase their self-reliance towards their built environment (housing). Design/methodology/approach: This paper elaborates on the setting in which the design support was tested within a quasi-experiment. The literature section describes the challenges in design research and why the DRM is suitable for this type of empirical research. Findings: Findings of the paper include a workable setting to organise and evaluate the impact of a design support within a DRM framework on a vulnerable rural community. Research limitations/implications: The main limitation of the research lies in the study population. Due to financial and time constraints, only four teams could participate in the experiment conducted in rural Kenya. Social implications: Further research will need to prove that the support works in comparable situations on the African continent. Originality/value: The quasi-experiment setting within a DRM framework could benefit researchers in comparable empirical investigations.